The Manhaj of Book Al-'Ujalah fi Al-Ahadith Al-Musalsalah by Muhammad Yasin Al-Fadani: Manhaj Kitab Al-‘Ujalah fi Al-Ahadits Al-Musalsalah Karya Muhammad Yasin Al-Fadani - Zizikri, Huriaini; Rahmi, Yulia (Takwil: Journal of Quran and Hadith Studies, 2023)
Sheikh Muhammad Yasin al-Fadani was a great Indonesian hadith scholar in the late 20th century. A scholar of Padang, West Sumatra who was born in Makkah and is famous in various parts of the world. The scholars recognized his knowledge by dubbing him as Musnid al-Dunya. He mastered various fields of Islamic science, especially regarding the science of hadith which focused on the sanad and matan of hadith. This research discusses the book of Al-'Ujalah fi Al-Ahadith Al-Musalsalah, one of the unique and rare written works, which is used as a source of reference for science, but there has been no research that focuses on this book to find out the method and content of the book's discussion. This research uses a combined method of character study and literature study, which aims to analyze the methodology he used both in the form of systematics and characteristics of writing the book "Al-'Ujalah fi Al-Ahadith Al-Musalsalah" as well as introducing his role and contribution during the study. The results of this study show that the book "Ujalah fi Al-Ahadith Al-Musalsalah" contains musalsal traditions with the most famous sanad network known by hadith scholars that are complete both in terms of sanad and matan, connected from one teacher to another, in the tradition of previous hadith scholars, up to the Prophet Muhammad. He then provides explanations and assessments of the musalsal traditions listed by several scholars as well as the authenticity of the traditions.